Level of Knowledge, Towards Sports Injuries of Elementary School Students, Sungai Tabukan District, North Hulu Sungai Regency - Adellia Susanti; Mita Erliana; Aryadi Rachman (Universitas Negeri Semarang, 2025)
The purpose of this study is to determine the level of knowledge about sports injuries of elementary school students in Sungai Tabukan District, North Hulu Sungai Regency. This study uses purposive sampling by taking a sample of 77 students from the population of 9 elementary schools in Sungai Tabukan District, North Hulu Sungai Regency, which totals 486 students. “This study uses a quantitative descriptive method. The results of this study show that the level of knowledge of students about sports injuries of elementary school students in Sungai Tabukan District, North Hulu Sungai Regency” is in the “very good” category of 6.5% (5 students), the “good” category is 26.0% (20 students), the “moderate” category is 42.9% (33 students), the “poor” category is 20.8% (16 students), and the “very poor” category is 3.9% (3 students) while based on the average score is 21.36. The conclusion of the research results of the research on the level of knowledge about sports injuries of elementary school students in Sungai Tabukan District, North Hulu Sungai Regency is in the “moderate” category.